2016
DOI: 10.1186/s12888-016-0862-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the UN convention on the rights of persons with disabilities (UN-CRPD) on mental health care research - a systematic review

Abstract: BackgroundThe United Nations Convention on the Rights of Persons with Disabilities (UN-CRPD) aims at stimulating profound changes and social development in many areas of the society. We wanted to examine the impact of the convention on mental health care research up to now by a systematic review.MethodsWe searched relevant electronic databases for empirical studies from the area of mental health which focused directly on the content of the UN-CRPD.ResultsOne thousand six hundred ten articles were screened, 36 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 41 publications
0
27
0
3
Order By: Relevance
“…3,4 The United Nations Convention on the Rights of Persons with Disabilities (UNCRPD) brought about a paradigm shift from a "charity-based" to a "rightsbased" perspective. 5 The Rights of Persons With Disabilities (RPWD) Act, 2016, was enacted in India with several new provisions from the "rights-based" perspective following UNCRPD. Reasonable accommodation (RA), defined as "necessary and appropriate adjustments, without imposing a disproportionate or undue burden in a particular case, to ensure to persons with disabilities, the enjoyment and exercise of rights equally with others" was a major inclusion in the Act.…”
mentioning
confidence: 99%
“…3,4 The United Nations Convention on the Rights of Persons with Disabilities (UNCRPD) brought about a paradigm shift from a "charity-based" to a "rightsbased" perspective. 5 The Rights of Persons With Disabilities (RPWD) Act, 2016, was enacted in India with several new provisions from the "rights-based" perspective following UNCRPD. Reasonable accommodation (RA), defined as "necessary and appropriate adjustments, without imposing a disproportionate or undue burden in a particular case, to ensure to persons with disabilities, the enjoyment and exercise of rights equally with others" was a major inclusion in the Act.…”
mentioning
confidence: 99%
“…Article 24 (education): Nine articles included in this review refer to specific indicators and personal outcomes related to inclusive education [ 8 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ] in ordinary settings at all levels of education (preschool, primary, secondary, high school, vocational training, university). The specific indicators mentioned were the right to attend educational establishments near their community; individualized supports within the general education system; assessment of individual support needs in environments that maximize academic and social development; completion of stages and appropriate transitions between them; coordination among the different professionals involved; training about rights; training about sexuality, reproduction and family planning (understanding what sexual relationships are, risks, benefits and alternatives; questions about sexuality can be freely raised and resolved); training and preparation for independent living (in real-life contexts, from compulsory education); vocational guidance; adequate training and qualifications to get a job; individualized educational aids (e.g., teacher’s aide, tutors, extended test time, modified course curriculum); appropriate materials; reasonable accommodations; quick access to necessary educational support products (e.g., specialized software, recording or note taking devices, audio/e-book devices); information, care, and guidance services for families (e.g., legislative measures and supports related to the education of their children); participation of the family in the education process; information, care, and guidance services for teachers about disability, supports and special educational needs; attitudes toward the inclusion of family members and teachers; meaningful learning experiences; participation in the activities of the school; the school and its staff enhance the person’s self-esteem, satisfaction, autonomy, and self-confidence; friends at school (not only among staff or carers); educational institutions in a holistic perspective of health and care.…”
Section: Resultsmentioning
confidence: 99%
“…While the debate regarding the United Nations Convention on the rights of persons with disabilities remains largely theoretical with few empirical studies (Steinert, Steinert, Flammer, & Jaeger, 2016), the field of therapeutic jurisprudence sheds more light on whether the involvement of mental health input in the law can lead to benefits. Indeed, empirical studies in therapeutic jurisprudence have shown support for lower recidivism and re-hospitalization rates, as well as higher levels of perceived procedural justice and involvement, indicating some success in the criminal realm of things (Cummings, 2010;Redlich & Han, 2014).…”
Section: Current Psycholegal Climatementioning
confidence: 99%